La naissance du quartier de la Poudrière (1) - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Armes; Femmes; Guerre; Verdun

Sur le chemin des tanks - Boucley, Pierre (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Armes; Guerre; Usines Angus

« Others of more entreprise »: Thomas Morland and the Formation of Montreal Rolling Mills, 1858-1868 - Mathieu, Jean-Philip (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Montreal Rolling Mills; Quartiers

De Lorimier 1895-1909 (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chaussure; De Lorimier (village); Parcs; Usines Angus

Le Plateau industriel (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Alimentation; Chaussure; Grèves; Plateau Mont-Royal (arrondissement); Travail; Vêtements

L'histoire des boissons gazeuses Corona - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Alimentation; Verdun

L’héritage contrasté de l’âge d’or du pétrole : histoire et évolution des paysages de l’est de Montréal - Hatton-Proulx, Clarence; Mercure Jolette, Frédéric; Van Neste, Sophie L. (Recherches sociographiques, 2023)
Keywords: Anjou; Montréal-Est; Paysages; Pollution; Pétrole

“La Grève de la fierté”: Resisting Deindustrialization in Montréal’s Garment Industry, 1977–1983 - Laframboise, Lauren (Labour / Le Travail, 2023)
Keywords: Femmes; Grèves; International Ladies' Garment Workers' Union; Vêtements

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

Fabriquer la tradition canadienne-française : le tabac canadien et la construction de l’identité canadienne-française, 1880-1950 - Rudy, Jarrett (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Tabac

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Juifs; Saint-Laurent (rue)

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Artisans; Carrière; Charretiers; Travail

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

Le travail du métal à Montréal au XVIIe siècle. Des métiers '' d’avenir '' ? - Blouin, Sonia (2022)
Keywords: Armuriers; Fer et acier

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

Patrimoine et développement local: le cas de l'édifice RCA - Dambre-Sauvage, Laurent (Bulletin de l'AQPI, 2022)
Keywords: Patrimoine

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman, William; Photographie; Publicité

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Prohibition-Brasserie Chapman-Microbrasseries - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2022)
Keywords: Alcool; Brasserie; Prohibition

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

L’importance des métaux dans une ville naissante : les artisans du métal dans l’espace social et urbain de Montréal de 1642 à 1701 - Blouin, Sonia (Université de Sherbrooke, 2021)
Keywords: Artisans; Fer et acier; Travail

La boulangerie Le Pain moderne canadien de Montréal. Les promesses du pain industriel - Burgess, Joanne (Cap-aux-Diamants, 2021)
Keywords: Alimentation; Boulangerie

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Les minoteries du canal de Lachine - Gelly, Alain (Cap-aux-Diamants, 2021)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie flour Mills

Petites et grandes boulangeries. La fabrication du pain dans le quartier Centre-Sud de Montréal - Giroux, Éric (Cap-aux-Diamants, 2021)
Keywords: Alimentation; Boulangerie; Centre-sud (quartier)

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Produits Familex: de l'usine à votre porte - Landreville, Julie (Bulletin de l'AQPI, 2021)
Keywords: Commerce de détail; Pharmacie; Produits pharmaceutiques

DOUGALL, JOHN REDPATH - MacLeod, Roderick (Dictionnaire biographique du Canada, 2021)

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
Keywords: Lachine (canal); Montreal Rolling Mills

Pour les femmes, par les femmes : une histoire entrepreneuriale de la presse féminine québécoise au tournant du XXe siècle - Rocher-Lewis, Delphine (Université du Québec à Montréal, 2021)
Keywords: Barry, Robertine; Bélanger, Georgina (De Montreuil, Gaétane / Bélanger, Georgine); Femmes; Journalistes; Marchand-Dandurand, Joséphine

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Saveur café (Mémoire vivante, 2020)
Keywords: Alimentation; Cafés; Restaurant; Épicerie

Saveur café: À l'origine du café de Gérard Van Houtte - Bizier, Hélène-Andrée (Mémoire vivante, 2020)
Keywords: Alimentation; Cafés; Restaurant; Épicerie

La Brasserie Dow. Tome 2: La chute - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2020)
Keywords: Brasserie; Dow (brasserie)

Futur parc sur la rue Marcel-Pepin. Un lieu riche en histoire - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Keywords: Chemins de fer; Hôpitaux; Itinérance; Usines Angus; Variole; Épidémies

"Ici, c'est le salon du peuple!" : microbrasseries, bières artisanales et communautés de consommation au Québec - Francoeur, Iannick (Université Laval, 2020)
Keywords: Brasserie; Molson (brasserie); National Breweries Limited

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

Une amitié nécessaire: entraide et fraternité dans le champ des comic books québécois (1984-1995) - Rioux, Philippe (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 2020)
Keywords: Bande dessinée; Librairie; Magasins; Édition

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Université Concordia, 2020)
Keywords: Femmes; Grèves; Textile

Transmettre le savoir et une vision du Canada aux jeunes Québécois: une étude de « L’Encyclopédie de la jeunesse » (1923) de la Société Grolier de Montréal - Bernier, Kristina (Université de Sherbrooke, 2019)
Keywords: Action française (L'); Nationalisme; Édition

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Angelina Di Bello: une grande dame de la couture - Mathieu, Jocelyne (Cap-aux-Diamants, 2019)
Keywords: Confection; Vêtements

Legal Persons and Asset Management Strategy: William Clendinneng and the Canada Pipe and Foundry Company - Simeone, Daniel (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Banque du Peuple; Banques; Fer et acier; Mouleurs

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

RUBENSTEIN, LOUIS - Vigneault, Michel (Dictionnaire biographique du Canada, 2019)

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie

Les céramiques et les réseaux maritimes du fort de Ville-Marie, Montréal, 1642-1688 - Bourgela, Samuel (Université de Montréal, 2018)
Keywords: Marchands; Port; Poterie

La filature Hudon - Charbonneau, Réjean; Cousineau, André (D'une track à l'autre, 2018)
Keywords: Hochelaga (quartier); Quartiers; Textile; Travail

La brasserie Dow. Tome 1: L'ascension - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2018)
Keywords: Brasserie; Dow (brasserie)

Through the Mill: Girls and Women in the Quebec Cotton Textile Industry, 1881-1951 - Cuthbert Brandt, Gail (Baraka Books, 2018)
Keywords: Femmes; Grèves; Textile; Travail

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Les défis de la sauvegarde du patrimoine à la Société d'histoire d'Ahuntsic-Cartierville - Labarussias, Jordane (Histoire Québec, 2018)
Keywords: Ahuntsic; Armes; Cartierville; Conservation; Femmes; Forts; Guerre; Histoire; Patrimoine; Quartiers; Sault-au-Récollet

Une note musicale! (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
Keywords: Chanson; Musicien; Musique

Nourrir le quartier, nourrir la ville - Burgess, Joanne; Giroux, Éric (Écomusée du fier monde, 2017)
Keywords: Alimentation; Biscuiterie; Boulangerie; Brasserie; Centre-sud (quartier); Magasins; Marchés; Quartiers; Épicerie

Eusèbe Senécal imprimeur-éditeur 1860-1902 - Cudia, Caroline (Université du Québec à Montréal, 2017)
Keywords: Imprimerie; Revue canadienne (La); Senécal, Eusèbe; Édition

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Angus: ADN et mutations génétiques - St-Cyr, Pierre (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
Keywords: Canadien Pacifique; Chemins de fer; Conservation; Patrimoine; Usines Angus

GORDON, SIR CHARLES BLAIR - Brown, Robert Craig (Dictionnaire biographique du Canada, 2016)

Confitures et marinades Raymond: faites pour plaire! - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
Keywords: Alimentation; Expositions; Musées; Écomusée du fier monde

La Centrale d’artisanat du Québec à Montréal - Mathieu, Jocelyne (Les Cahiers des Dix, 2016)
Keywords: École des Beaux-Arts; École des arts graphiques; École du meuble

Au chant des ailes des moulins - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Meunerie

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

100 tonnes d'explosifs stockés sur l'avenue Dunlop! Intolérable! - Lester, Normand (Mémoire vivante, 2015)
Keywords: Armes; Forts; Rébellions

1900. Pourquoi pas un gram-o-phone Berliner? - P. Bouliane, Sandria (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Chanson; Gramophone; Musique

LEVINSON, SOLOMON - Lapidus, Steven (Dictionnaire biographique du Canada, 2014)

Émergence et évolution d’une profession artistique: les dessinateurs de presse entre 1880 et 1914 à Montréal - Danaux, Stéphanie (Médias 19, 2013)
Keywords: Caricature; Gravure; Patrie (La)

Esthétique de la typographie: Roland Giguère, les Éditions Erta et l'École des arts graphiques - Dulude, Sébastien (Convergences, 2013)
Keywords: École des arts graphiques; Édition

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

GRAHAM, HUGH, 1er baron ATHOLSTAN - Raudsepp, Enn (Dictionnaire biographique du Canada, 2013)

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

Pointe-Saint-Charles: histoire de locomotives - Bélisle, Jean (Bulletin de l'Association québécoise pour le patrimoine industriel, 2012)
Keywords: Canadien National; Chemins de fer; Grand Tronc

Le système régional d’innovation de l’aéronautique à Montréal: entre dynamiques territoriales et sectorielles - Ben Hassen, Tarek (Université du Québec à Montréal, 2012)
Keywords: Avionnerie

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Sarto Desnoyers, l'homme aux tâches multiples 1904-1996 / Sarto Desnoyers, Jack of All Trades 1904-1996 - Garneau, André (Héritage Dorval, 2012)
Keywords: Chevaux; Dorval; Hockey; Maires; Palestre nationale; Pharmacie; Produits pharmaceutiques

Héritage Dorval 2011 (Héritage Dorval, 2011)
Keywords: Bijouterie; Chaussure; Dentistes; Hôtellerie; Magasins; Quincaillerie; Restaurant; Électricité

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

Grandeur et déclin de la pétrochimie sur le territoire historique de la Pointe-aux-Trembles et de Montréal-Est - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2011)
Keywords: Montréal-Est; Pointe-aux-Trembles; Pétrole; Quartiers

Intervention publique sur le développement de grappes industrielles au Québec - Doloreux, David; Tremblay, Diane-Gabrielle; Klein, Juan-Luis; Dionne, Steve; Ben Hassen, Tarek (The Canadian Geographer / Le Géographe canadien, 2011)

Étude urbaine d'un îlot du faubourg Saint-Laurent: la confection sur la Main, 1880-1939 - Lacaille, Marie-Ève (Université du Québec à Montréal, 2011)
Keywords: Confection; Faubourgs; Juifs; Quartiers; Rues; Saint-Laurent (quartier); Saint-Laurent (rue)

Le moulin de Pointe-Claire, 1710-2010 / 1710-2010, The Pointe-Claire Mill - Arsenault, Claude (Société pour la sauvegarde du patrimoine de Pointe-Claire, 2010)
Keywords: Meunerie; Pointe-Claire

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

Éditeur de livres et de brochures - Bennett, Paul (Le Devoir: un siècle québécois, 2010)
Keywords: Devoir (Le); Édition

L'atelier des Écores (1792-1830): Une entreprise artisanale - Chagnon, Joanne (Université du Québec à Montréal, 2010)
Keywords: Artisans; Arts sacrés; Pépin, Joseph; Quévillon, Louis; Sculpture

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

La production du manuel scolaire congréganiste au Québec. Le cas de l'atelier d'imprimerie des Frères des écoles chrétiennes, 1891-1918 - Laforce, Guillaume (Université Laval, 2010)
Keywords: Communautés religieuses; Frères des écoles chrétiennes; Imprimerie

Angus Shop - Leduc, Michael (Michael Leduc, 2010)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

1870: du journal d'opinion à la presse de masse, la production industrielle de l'information - Leroux, Éric (Petit musée de l'impression et Centre d'histoire de Montréal, 2010)
Keywords: Asselin, Olivar; Bourassa, Henri; Buies, Arthur; Devoir (Le); Idéologies; Imprimerie; Journalistes; Lanterne (La); Lovell, John; Montreal Star; Nationalisme; Nationaliste (Le); Patrie (La); Presse (La)

Dossier: Histoire du meuble - Loubert, Huguette; Ouellet, Richard (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2010)
Keywords: Artisans; Plateau Mont-Royal; Quartiers; Sculpture; Ébénistes

The Long, Angry Summer of ’43: labour Relations in Quebec’s Shipbuilding Industry - Pritchard, James (Labour / Le travail, 2010)
Keywords: Construction navale

Les Livrets de spécimens typographiques de Lovell & Gibson, 1846 et 1847 - Virr, Richard (1870: du journal d'opinion à la presse de masse, la production industrielle de l'information, 2010)
Keywords: Imprimerie; Lovell, John

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

The Life of James Coristine: from Griffintown to the Square Mile - Coristine, Cynthia; Browness, Ian (C. Coristine et I. Browness, 2009)
Keywords: Confection; Fourrure; Marchands; Vêtements

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

Le développement de la presse depuis la Conquête jusqu'à l'Union - Doyon, Nova (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Minerve (La); Montreal Gazette; Montreal Herald

De couturière à Soeur Grise. Le parcours inhabituel de Marie Catherine Demers Dessermon dans le Montréal du XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2009)
Keywords: Communautés religieuses; Confection; Soeurs Grises

L’industrie et l’espace urbain. Étude de l’évolution physique du site de la compagnie Dominion Glass, avenue De Lorimier, à Montréal, 1878-1947 - Lampron, Amélie (Université du Québec à Montréal, 2009)
Keywords: Dominion Glass Company

Ludger Duvernay, le journal La Minerve et la construction identitaire canadienne - Monière, Denis (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Journalistes; Minerve (La); Rébellions; Société Saint-Jean-Baptiste

1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone - Doyon, Nova (Petit musée de l'impression et Centre d'histoire de Montréal, 2009)
Keywords: Duvernay, Ludger; Imprimerie; Journalistes; Loyalistes; Minerve (La); Montreal Gazette; Montreal Herald

Angus, du grand capital à l’économie sociale - Nadeau, Gaétan (Fides, 2009)
Keywords: Canadien Pacifique; Chemins de fer; Travail; Usines Angus

Bombardier: A Dream with International Reach, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Bombardier: l'internationalisation d'un rêve, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury

1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal - Ruelland, Jacques G. (Petit musée de l'impression et Centre d'histoire de Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury; Montreal Gazette

L'Académie de Montréal - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Mesplet, Fleury

Premier imprimeur-libraire à Montréal: Fleury Mesplet (1734-1794), un défenseur des droits humains - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet, Fleury; Montreal Gazette

Fleury Mesplet: le pouvoir de la Presse - de Lagrave, Jean-Paul; Ruelland, Jacques G. (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet, Fleury; Montreal Gazette

Design, Presentation Silver and Louis-Victor Fréret (1801-1879) in London and Montreal - Fox, Ross (Material Culture Review / Revue de la culture matérielle, 2008)
Pas dans la période V car il n'est pas à Montréal avant 1867 de ce que nous (JRL) comprenons
Keywords: Artisans; Sculpture

Territoire, patrimoine, quartier en développement: le cas de la zone Chabanel au centre-nord de la ville de Montréal - Mariani, Alessandra (Patrimoines: fabrique, usages et réemplois, 2008)
Keywords: Patrimoine; Quartiers

John Molson. Sa vie, son oeuvre - Daignault, Sylvain (Célébrités / Collection biographique, 2007)
Keywords: Hommes d'affaires; Molson (brasserie)

L'essor du livre illustré au Québec en relation avec les milieux artistiques et éditoriaux français: 1880-1940 - Danaux, Stéphanie (Université de Montréal et Université de Poitiers, 2007)
Keywords: Édition

L’École du meuble de Montréal: au-delà de l’ébénisterie - Dubois, Martin (Continuité, 2007)
Keywords: Ébénistes; École du meuble

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

Réaménager la tradition - Gaudreau, Valérie (Continuité, 2007)
Keywords: Ébénistes; École du meuble

Une économie sur ses rails: la contribution du "6000 Saint-Denis" au développement du nord de Montréal - Laplace, Josée (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
Keywords: Montreal Street Railway Company; Patrimoine; Tramways; Transport en commun

Pointe St. Charles Shop - Leduc, Michael (Michael Leduc, 2007)
Keywords: Chemins de fer; Grand Tronc

Étude de cas. La formation des imprimeurs: L'École des arts graphiques de Montréal. - Leroux, Eric (Histoire du livre et de l'imprimé au Canada, vol. III (1918-1980), 2007)
Keywords: Imprimerie; École des arts graphiques

"Nous ne voulons pas que nos héritiers soient à la merci des tiens": famille, patrimoine et entreprise chez les Rolland, 1880-1980 - Nootens, Thierry (Revue d'histoire de l'Amérique française, 2007)
Keywords: Famille; Patrimoine

Mobilier québécois au MBAM: regards dans le temps et l’espace - Pepall, Rosalind (Continuité, 2007)
Keywords: Musée des Beaux-Arts; Musées

La fabrication culturelle d’un cigare à Montréal au tournant du vingtième siècle - Rudy, Jarrett (Tabac et fumées: regards multidisciplinaires et indisciplinés sur le tabagisme XVe-XXe siècles, 2007)
Keywords: Tabac

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

At the End of the Final Line. A Brief History of Aircraft Manufacturing at Canadian Vickers and Canadair - Campbell, Patrick J. (Shoreline, 2006)
Keywords: Avionnerie; Canadair; Canadian Vickers

Aspects of Scottish-Canadian Material Culture: Heart Brooches and Scottish Pottery - Dalgleish, George R. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Orfèvres; Poterie; Écossais

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath, John; Sucre

Les grands de l’aéronautique: Canadian Vickers, Canadair, Bombardier - Fortier, Rénald (Cap-aux-Diamants, 2006)
Keywords: Avionnerie; Bombardier; Canadair; Canadian Vickers

La représentation de l'industrie dans les guides bruxellois et montréalais au tournant du 20e siècle - Kenny, Nicolas (Cahiers de la Fonderie, 2006)
Keywords: Fer et acier; Tourisme

Artisans et industries en milieu rural au Québec avant 1851. L’exemple de l’Île Jésus - Logette, Jérôme (Université du Québec à Montréal, 2006)
Keywords: Artisans; Île Jésus

Hartland de Montarville Molson: man of honour - Molson, Karen (Firefly Books, 2006)
Keywords: Brasserie; Hommes d'affaires; Molson (famille)

La fabrique de pipes à fumer Henderson: inventaire archéologique sur le site Henderson-Dixon, BjFj-135, Montréal, 2005. Arrondissement Ville-Marie - Roy, Christian (Patrimoine archéologique de Montréal, 2006)
Keywords: Artisans; Tabac

Habiter, prendre pied, s'établir. Les commerçants et manufacturiers juifs de Montréal, 1918-1930 - Taschereau, Sylvie (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Juifs

A Scottish-born Silversmith in Montreal: Robert Cruikshank - Villeneuve, René (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Orfèvres; Écossais

DAVIS, sir MORTIMER BARNETT - Burgess, Joanne (Dictionnaire biographique du Canada, 2005)

Les Forget, luthiers depuis un siècle - Desjardins, Marie (Éditions au Carré, 2005)
Keywords: Artisans; Musique

Les entreprises d'imprimerie et d'édition en Amérique du Nord britannique, 1751-1840 - Hare, John; Wallot, Jean-Pierre (Mens, 2005)
Keywords: Imprimerie; Édition

La formation professionnelle des ouvriers des métiers du livre au Québec au XXe siècle - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2005)
Keywords: Imprimerie; École des arts graphiques; École technique

Étude de cas. Abraham de Sola, éditeur juif dans le Montréal victorien - Menkins, Richard (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: De Sola, Abraham; Juifs

STEPHEN, GEORGE, 1er baron Mount Stephen - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

LESPÉRANCE, ZOTIQUE - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Histoire de la raffinerie de Petro-Canada à Montréal, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

History of Petro-Canada Montreal refinery, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

RICHARD, MAURICE, dit le Rocket - Vigneault, Michel (Dictionnaire biographique du Canada, 2005)

Les manuels scolaires en Nouvelle-France dans la « Province du Québec » et au Bas-Canada - Aubin, Paul (Histoire du livre et de l'imprimé au Canada, vol. I (des débuts à 1840), 2004)
Keywords: Collège de Montréal; Congrégation de Notre-Dame; Frères Charon; Imprimerie

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Un essor laborieux : l'électricité et le monde industriel. Les choix énergétiques des entrepises du canal de Lachine, Montréal, 1880-1920 - Gelly, Alain (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

La culture urbaine au Canada et les formes de la culture de l'imprimé aux XVIII et XIX siècles - Lamonde, Yvan (Urban History Review / Revue d'histoire urbaine, 2004)
Keywords: Imprimerie; Librairie; Édition

A City Transformed: Manufacturing Disctricts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Manufacturing Suburbs. Building Work and Home on the Metropolitan Fringe, 2004)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

The Association of Canadian Couturiers - Palmer, Alexandra (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Les industries à LaSalle de 1912 à 2002 - Zaïd, Omar; Zitouni, Khadoudja (Société historique Cavelier-de-LaSalle, 2004)
Keywords: LaSalle

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Navigation; Énergie hydraulique

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Patrimoine archéologique de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

Syndicats et collectivités dans la gouvernance locale: une recherche exploratoire à Montréal - Klein, Juan-Luis; Fontan, Jean-Marc (Recherches sociographiques, 2003)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Le grain, la meule et les vents: le métier de meunier en Nouvelle-France - Laperle, Dominique (GID, 2003)
Keywords: Meunerie

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Aqueduc; Énergie hydraulique

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

L'industrie de la chaussure à Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Travail et syndicalisme: naissance et évolution d'une action sociale, 2002)
Keywords: Artisans; Chaussure

Montréal, 1870-1970: portrait de l’industrie laitière urbaine - Burgess, Joanne (Cap-aux-Diamants, 2002)
Keywords: Lait

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

Intermodal Freight Terminals: Locality and Industrial Linkages - McCalla, Robert J.; Slack, Brian; Comtois, Claude (The Canadian Geographer / Le Géographe canadien, 2001)
Keywords: Aéroport; Chemins de fer; Port

A City Transformed: Manufacturing Districts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Journal of Historical Geography, 2001)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Les communautés religieuses et l'édition du manuel scolaire au Québec, 1765-1964 - Aubin, Paul (Groupe de recherche sur l'édition littéraire au Québec, 2001)
Keywords: Communautés religieuses; Enseignants; Édition

La ville, agent catalyseur de développement: le rôle des municipalités dans l’évolution de l’industrie canadienne des véhicules d’incendie, 1945-1965 - Beauvais, Suzanne (Material History Review / Revue d’histoire de la culture matérielle, 2001)
Keywords: Incendies; Pompiers

Ces machines qui chantent… - Bélisle, Jean; Cloutier, Nicole (Continuité, 2001)
Keywords: Musique; Radio

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

De génération en génération: la transmission des savoir-faire - Simard, Cyril (Cap-aux-Diamants, 2001)
Keywords: Artisans

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

La saga du technopôle Angus: reconversion productive et reconversion sociale - Klein, Juan-Luis; Fontan, Jean-Marc; Tremblay, Diane-Gabrielle; Bordeleau, Danièle (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Usines Angus

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Brasseurs, brasseries et activités brassicoles dans la plaine de Montréal, 1788-1852 - Morin, Stéphane (Université du Québec à Montréal, 2000)
Keywords: Brasserie

Les techniques et le commerce de la tannerie à Montréal au XVIIIe siècle - Perrier, Jocelyne (Scientia Canadensis, 2000)
Keywords: Artisans; Marchands; Tannerie